Factors of digitalization of the transport complex of the Russian Federation - V. S. Gorin; A. O. Merenkov; G. A. Lastochkina (Путеводитель предпринимателя)
The current stage of development of the transport complex of the Russian Federation is characterized by digital transformation. The author’s study is devoted to the description and assessment of the digitalization factors of the Abstract: The current stage of development of the transport complex of the Russian Federation is characterized by digital transformation. The author’s study is devoted to the description and assessment of the digitalization factors of the transport systems of Russia, with the identification of the main transformation trends in various areas of the transport and logistics business. The authors determined the digital track algorithm in the management of modern passenger services, the trends in the digital freight transportation segment. The conclusion describes the cybersecurity factor as the main risk of digitalization.